The effect of auditory rhythm on the temporal allocation of visual attention in aging - Zhihan Xu; Juan Huang; Yuxuan Shen; Yanna Ren; Yulin Gao; Ting Guo (Frontiers in Psychology)
IntroductionIsochronous rhythm has been shown to induce temporal expectation, allocated attention to specific points in time to optimize behavioral performance, both within a single modality and across different modalities, in younger adults. However, it remains unclear how an isochronous rhythm in one modality influences the temporal allocation of attention in another modality among older adults. Moreover, whether the cross-modal temporal expectation effect in aging is influenced by tempo has not yet been explored.MethodsTo address these issues, both younger and older participants performed a rhythmic temporal expectation task in which auditory isochronous rhythms, presented at either 600 ms (faster) or 1,400 ms (slower) tempo, were used to trigger temporal expectation for a visual target.ResultsThe results demonstrated a cross-modal temporal expectation effect, with participants exhibiting significantly faster responses when the visual target appeared in synchrony with the preceding auditory rhythm compared to out-of-synchrony trials. This effect was evident in both younger and older groups and was not influenced by tempo.DiscussionThese findings suggest that the ability to utilize auditory isochronous rhythms to drive the temporal allocation of visual attention can be preserved in normal aging, highlighting the robustness of cross-modal temporal expectations across both younger and older adults.